2011
DOI: 10.1016/j.rser.2011.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of biodiesel from soybean, jatropha and microalgae in China conditions

Abstract: Increasing demand for transport fuels has driven China to attach great importance to biodiesel development. To evaluate the environmental impacts caused by producing and driving with biodiesel made from soybean, jatropha, and microalgae under China conditions, the LCA methodology is used and the assessment results are compared with fossil diesel. The solar energy and CO 2 uptake in biomass agriculture and reduction of dependency on fossil fuels lead to a better performance on abiotic depletion potential (ADP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(68 citation statements)
references
References 34 publications
4
58
1
5
Order By: Relevance
“…The pollutants released from the production of electricity consist mostly of heavy metals (41.3%) such as arsenic (+V) and selenium, inorganic emissions to air (23.2%) and organic emissions to air (23.5%) for in situ transesterification. This result is in agreement with findings in earlier studies [27] that emissions of heavy metals are responsible for human toxicity.…”
Section: Eutrophication Potentialsupporting
confidence: 94%
See 2 more Smart Citations
“…The pollutants released from the production of electricity consist mostly of heavy metals (41.3%) such as arsenic (+V) and selenium, inorganic emissions to air (23.2%) and organic emissions to air (23.5%) for in situ transesterification. This result is in agreement with findings in earlier studies [27] that emissions of heavy metals are responsible for human toxicity.…”
Section: Eutrophication Potentialsupporting
confidence: 94%
“…GaBi revealed that NH 3 is the major pollutant leading to the effect of eutrophication. Similar findings have been observed in earlier studies [27]. From Fig.…”
Section: Eutrophication Potentialsupporting
confidence: 92%
See 1 more Smart Citation
“…The same occurs with studies on soybean LCA that have been carried out to date (e.g. Kim & Dale, 2009;Panichelli et al, 2009;Hou et al, 2011;Mohammadi et al, 2013). Moreover, most previous studies were limited to energy and GHG emissions, thus excluding other environmental impacts that are relevant throughout the agricultural process.…”
Section: Introductionmentioning
confidence: 78%
“…These parameters are algae productivity and oil content on dry mass of algae [33], and algae concentration in ponds. Here, we conduct a Monte-Carlo analysis testing the distribution of each parameter one by one in order to evaluate its influence on GHG emissions result of the entire system.…”
Section: Sensitivity Of Main Parameters For Ghg Emissionsmentioning
confidence: 99%